Effect of fenugreek seed aqueous extract on prevention of ovarian hyperstimulation syndrome in a rat model - Ben Hameid, Asma Saad Mahmoud (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Ovarian hyperstimulation syndrome (OHSS) is a life threatening iatrogenic condition associated with an increased in vascular permeability (VP). This study was aimed to explore the potential effects of fenugreek seeds aqueous extract (FSAE) on prevention of OHSS in rats. Thirty-four immature, female Sprague Dawley rats, at the age of 18 days post-natal (PN) with body weight around 40 grams were randomly divided into negative control (NC), positive control (PC), and treated (T) groups. The T group rats were treated with FSAE at dose 1500mg/kg body weight/day for thirteen days. The OHSS was induced in both (PC) and (T) groups by using Pregnant Mare's Serum Gonadotropin (PMSG) and human Chorionic Gonadotropin (hCG). From day 8 to11 (PN 25-28), rats of PC and T were injected subcutaneously (SC) with (50 IU/day) of PSMG. On day 12 (PN 29) rats were injected with 25 IU of hCG. On Day 14 (PN 31) rats were injected with 0.2 ml of 5mM Evan's Blue dye (EBD) into the femoral vein under anaesthesia. After 30 minutes, the rats were decapitated. The effect of FSAE was evaluated by measuring the VP, VEGF, oestradiol (E2), along with relative ovarian weight and ovarian histological study. Results showed that the FSAE decreases VP of OHSS treated group significantly. There was a significant increase in relative ovarian weight in treated group. FSAE has no significant effect on primary and secondary ovarian follicles and corpora lutea follicles. Graafian follicles is higher in treated group. Atretic follicles were increased significantly in treated group. FSAE reduced significantly serum E2 level in treated group. While no change in serum VEGF was observed. Concluding that the FSAE may has the ability to prevent OHSS by decreasing the VP and serum E2, and by increasing atretic follicles. Keywords: OHSS, Fenugreek, Vascular permeability.